Uji Efektifitas Ekstrak Daun Sirih Hijau (Piper betle L) dan Ekstrak Daun Pepaya (Carica papaya L) Terhadap Mortalitas Larva Nyamuk Aedes aegypti L - Blasius Atini; Yulianti Rika; Ludgardis Ledheng (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
Dengue fever is an infectious disease caused by a virus transmitted by the mosquito Aedes aegypti L. One of the DBD vector eradication programs involves using synthetic insecticides. The use of synthetics (chemicals) is known to be very effective, relatively easy, and practical, but it has a negative impact on the environment. One is using natural insecticides; in this way, it is expected to inhibit the life cycle of mosquitoes before they develop to adulthood. The natural insecticide used is a plant insecticide from the green leaf plant (Pipper betle L) and the leaf of the papaya (Carica papaya L), because both plants have a secondary metabolite compound that can inhibit the growth of the larvae of the mosquito Aedes aegypti L. The method in this study is a simple experimental design with a complete random effect (RAL) to see the effectiveness of extracts of green coriander leaves and papaya leaves. With each extract being tested for its effectiveness, three treatments and one control were performed. The research using the extraction method, i.e., the mazeration method of observing larval death, was conducted for 1 hour of observation to determine the effectiveness of treatment extracts tested using Anova level 5% and probit analysis to determine LC50 values. The average mortality of mosquito larvae (Aedes aegypti L) after treatment with ethanol extract of green syrup leaves at a concentration of 60% at 100%, at a concentration of 40% at 87%, and at a concentration of 20% at 47%.